2013
DOI: 10.1128/aem.02359-12
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterial Succession and Correlation Networks in a Large Unselected Cohort of Mothers and Their Children

Abstract: c Bifidobacteria are a major microbial component of infant gut microbiota, which is believed to promote health benefits for the host and stimulate maturation of the immune system. Despite their perceived importance, very little is known about the natural development of and possible correlations between bifidobacteria in human populations. To address this knowledge gap, we analyzed stool samples from a randomly selected healthy cohort of 87 infants and their mothers with >90% of vaginal delivery and nearly 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 41 publications
(41 reference statements)
3
65
0
Order By: Relevance
“…The dominance of B. breve in the gut community has been supported by several studies, especially in breast-fed infants (11,14), where this species together with B. longum subsp. longum and B. longum subsp.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The dominance of B. breve in the gut community has been supported by several studies, especially in breast-fed infants (11,14), where this species together with B. longum subsp. longum and B. longum subsp.…”
Section: Discussionmentioning
confidence: 72%
“…infantis, B. longum subsp. longum, Bifidobacterium catenulatum, Bifidobacterium pseudocatenulatum, and Bifidobacterium bifidum are the species most frequently detected in breast-fed infant feces (11,14,33). In general, B. breve and B. longum subsp.…”
mentioning
confidence: 99%
“…Originally, the fetal gastrointestinal (GI) tract is sterile. The establishment of the gut microbiota is immediately initiated at birth and characterized by a dynamic succession of bacterial populations until a homeostatic adult‐like microbiota is established by the age of 2–3 years . Thus, these high basal calprotectin levels could be due to a higher intestinal permeability, the establishment of gut flora, and a response to alimentary antigens, as well as to the colonization of the gut by commensal microbes, which help to prevent enteric pathogen infections and block the interactions between the pathogens and the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that Bifidobacterium is a predominant genus in the microbiota of breast-fed infants (Harmsen et al, 2000;Yatsunenko et al, 2012). longum (B. longum) and, to a lesser extent, Bifidobacterium catenulatum, Bifidobacterium pseudocatenulatum, and Bifidobacterium bifidum (Avershina et al, 2013;Ruiz-Moyano et al, 2013;Turroni et al, 2012a). infantis (B. infantis), Bifidobacterium longum subsp.…”
Section: Intestinal Microbiota In Breast-fed Infantsmentioning
confidence: 99%